The Byte guide to CP/M-86 / a novel - Obst, Lynda Rosen; Wolper, Carol (New York : Nal Books, 1990)
Two women, a screenwriter and a studio executive, wage war against a sleazy Hollywood producer who is using blackmail, sexual pressure, and his ties to the underworld to promote a racy new film project called "Dirty Dreams".
Keywords: DIRTY DEALS -- FANTASY FICTION